17β-Estradiol Protects Neural Stem/Progenitor Cells Against Ketamine-Induced Injury Through Estrogen Receptor β Pathway - Li, Weisong; Lu, Pan; Lu, Yang; Wei, Haidong; Niu, Xiaoli; Xu, Jing; Wang, Kui; Zhang, Hong; Li, Rong; Qiu, Zhengguo; Wang, Ning; Jia, Pengyu; et al. (Frontiers in Neuroscience, 2020)
Ketamine inhibits neural stem/progenitor cell (NSPC) proliferation and disrupts normal neurogenesis in the developing brain. 17β-Estradiol alleviates neurogenesis damage and enhances behavioral performance after ketamine administration. However, the receptor pathway of 17β-estradiol that protects NSPCs from ketamine-induced injury remains unknown. In the present study, we investigated the role of estrogen receptor α (ER-α) and estrogen receptor β (ER-β) in 17β-estradiol’s protection against ketamine-exposed NSPCs and explored its potential mechanism. The primary cultured NSPCs were identified by immunofluorescence and then treated with ketamine and varying doses of ER-α agonist 4,4′,4″-(4-propyl-[1H]-pyrazole-1,3,5-triyl) trisphenol (PPT) or ER-β agonist 2,3-bis(4-hydroxyphenyl)-propionitrile (DPN) for 24 h. NSPC proliferation was analyzed by 5-bromo-2-deoxyuridine incorporation test. The expression of phosphorylated glycogen synthase kinase-3β (p-GSK-3β) was quantified by western blotting. It was found that treatment with different concentrations of PPT did not alter the inhibition of ketamine on NSPC proliferation. However, treatment with DPN attenuated the inhibition of ketamine on NSPC proliferation at 24 h after their exposure (P < 0.05). Furthermore, treatment with DPN increased p-GSK-3β expression in NSPCs exposed to ketamine. These findings indicated that ER-β mediates probably the protective effects of 17β-estradiol on ketamine-damaged NSPC proliferation and GSK-3β is involved in this process